PENGEMBANGAN MEDIA BUKU BERGAMBAR MABARUNG (MACAM-MACAM BANGUN RUANG) UNTUK PEMBELAJARAN MATEMATIKA KELAS 5 SD - Uli Ajnikhah; Henry Januar Saputra; Veryliana Purnamasari (JANACITTA, 2020)
The purpose of this study was to determine student responses after using learning media that have been developed, namely Mabarung picture books (various types of Building Space). The test was conducted in class 5 SDN 02 Bugangan Semarang and students in grade 5 SDN 01 Bugangan Semarang. The research method used is development research. the final stage in this study was the researcher used a student questionnaire in collecting data. The questionnaire was in the form of 20 statements regarding learning that had been done using MABARUNG media. The results of the questionnaire analysis of student responses at SDN 02 Bugangan showed a percentage of 96.25% and at SDN 01 Bugangan showed a percentage of 97.50%, meaning that MABARUNG media could foster interest and enthusiasm of students in learning mathematics and could facilitate students in understanding building material space is packed into a story.Keywords: Development, Mabarung Picture Book (Various Types of Space Building).